Deer do not affect short‐term rates of vegetation recovery in overwash fans on Fire Island after Hurricane Sandy. Issue 20 (6th October 2019) - Kilheffer, Chellby R.; Underwood, H. Brian; Raphael, Jordan; Ries, Lindsay; Farrell, Shannon; Leopold, Donald J.
Abstract: Coastal resilience is threatened as storm‐induced disturbances become more frequent and intense with anticipated changes in regional climate. After severe storms, rapid recovery of vegetation, especially that of dune‐stabilizing plants, is a fundamental property of coastal resilience. Herbivores may affect resilience by foraging and trampling in disturbed areas. Consequently, assessing the impacts of herbivores on recovering vegetation is important for coastal land management. We combined imagery classification, wildlife monitoring, and trend analysis to investigate effects of white‐tailed deer on recovery rates of vegetation four years poststorm in nine overwashed areas. We estimated local deer density with trail cameras, how it relates to an index of primary productivity, and assessed the relationship between deer density and rates of vegetation recovery in overwash fans. Prestorm vegetation cover consisted of shrubs and sporadic patches of beach grass. Poststorm cover was dominated by beach grass. At current rates, vegetation coverage will return to prestorm conditions within the decade, though community transition from grasses to shrubs will take much longer and will vary by site with dune formation. The effect of deer on rates of vegetation recovery was negative, but not statistically significant nor biologically compelling. Although effects of deer trampling on beach grass are evident in classified imagery, deer foraging on beach grass had little effect on its rate of spread throughout overwash fans. While the rate of spread of the primary dune‐building grass was not deleteriously affected by deer, locally high deer densities will likely affect the future establishment and development of herbs and shrubs, which are generally more palatable to deer than beach grass. Abstract : A dense white‐tailed deer population did not affect the rate of dune vegetation recovery after a large‐extent hurricane. Deer may, however, affect establishment and development of palatable plant species as disturbed areas continue to recover.